Mineralocorticoid receptor antagonism by finerenone is sufficient to improve function in preclinical muscular dystrophy. (18th September 2020) - Lowe, Jeovanna; Kolkhof, Peter; Haupt, Michael J.; Peczkowski, Kyra K.; Rastogi, Neha; Hauck, J. Spencer; Kadakia, Feni K.; Zins, Jonathan G.; Ciccone, Pierce C.; Smart, Suzanne; Sandner, Peter; Raman, Subha V.; et al.
Abstract: Aims: Duchenne muscular dystrophy (DMD) is an X‐linked inherited disease due to dystrophin deficiency causing skeletal and cardiac muscle dysfunction. Affected patients lose ambulation by age 12 and usually die in the second to third decades of life from cardiac and respiratory failure. Symptomatic treatment includes the use of anti‐inflammatory corticosteroids, which are associated with side effects including weight gain, osteoporosis, and increased risk of cardiovascular disease. Novel treatment options include blockade of the renin–angiotensin–aldosterone system, because angiotensin as well as aldosterone contribute to persistent inflammation and fibrosis, and aldosterone blockade represents an efficacious anti‐fibrotic approach in cardiac failure. Recent preclinical findings enabled successful clinical testing of a combination of steroidal mineralocorticoid receptor antagonists (MRAs) and angiotensin converting enzyme inhibitors in DMD boys. The efficacy of MRAs alone on dystrophic skeletal muscle and heart has not been investigated. Here, we tested efficacy of the novel non‐steroidal MRA finerenone as a monotherapy in a preclinical DMD model. Methods and results: The dystrophin‐deficient, utrophin haploinsufficient mouse model of DMD was treated with finerenone and compared with untreated dystrophic and wild‐type controls. Grip strength, electrocardiography, cardiac magnetic resonance imaging, muscle force measurements, histological quantification, and gene expression studies were performed. Finerenone treatment alone resulted in significant improvements in clinically relevant functional parameters in both skeletal muscle and heart. Normalized grip strength in rested dystrophic mice treated with finerenone (40.3 ± 1.0 mN/g) was significantly higher ( P  = 0.0182) compared with untreated dystrophic mice (35.2 ± 1.5 mN/g). Fatigued finerenone‐treated dystrophic mice showed an even greater relative improvement ( P  = 0.0003) in normalized grip strength (37.5 ± 1.1 mN/g) compared with untreated mice (29.7 ± 1.1 mN/g). Finerenone treatment also led to significantly lower ( P  = 0.0075) susceptibility to limb muscle damage characteristic of DMD measured during a contraction‐induced injury protocol. Normalized limb muscle force after five lengthening contractions resulted in retention of 71 ± 7% of baseline force in finerenone‐treated compared with only 51 ± 4% in untreated dystrophic mice. Finerenone treatment also prevented significant reductions in myocardial strain rate ( P  = 0.0409), the earliest sign of DMD cardiomyopathy. Moreover, treatment with finerenone led to very specific cardiac gene expression changes in clock genes that might modify cardiac pathophysiology in this DMD model. Conclusions: Finerenone administered as a monotherapy is disease modifying for both skeletal muscle and heart in a preclinical DMD model. These findings support further evaluation of finerenone in DMD clinical trials.